A comparative exergo-economic analysis of four configurations of carbon dioxide direct-expansion geothermal heat pump. (25th December 2019) - Ghazizade-Ahsaee, Hossein; Ameri, Mehran; Baniasad Askari, Ighball
Highlights: Exergy-economic analysis of four CO2 DX-GHP is developed. The effect of expander and IHE in CO2 DX-GHP is investigated. Two cases with constant a) SH and b) DHW loads are studied. Shown that the (EVC + IHE) and (EC + IHE) have the lowest c q and the highest η e x . Shown that the configuration with the highest η e x is not that with the lowest c q . Abstract: The present paper deals with a comparative exergo-economic analysis among four different horizontal Direct-Expansion Geothermal Heat Pumps (DX-GHP) with Carbon Dioxide ( C O 2 ) refrigerant in transcritical cycle. The studied configurations include the cycle with (a) expansion valve (EVC), (b) with expander (EC), (c) with expansion valve and Internal Heat Exchanger (EVC + IHE), and (d) with expander and IHE (EC + IHE). The unit cost of heat ($/ k W h e x ) for each configuration was determined under two scenarios of a) constant Space Heating (SH) and b) constant Domestic Hot Water (DHW) loads with the peak of 8 kW. The results showed that the lowest unit cost of heat ( c q ) and the highest total exergy efficiency ( η e x ) are associated with the (EVC + IHE) and (EC + IHE) configurations, respectively. Also, it was shown that for the SH (or DHW) load, 20% (or 14%) increase in the η e x results in 21.5% (or 20%) increase in the c q considering the electricity cost of 0.025 $/kWh. For the electricity cost of 0.25 $/kWh, however, 11% (or 20%) increase in η e x results in increasing the c q by about 7% (or 13%). It was also concluded that the configuration with the highest η e x is not that with the lowest c q .